Cross-platform hatedom: Influencers’ strategies for managing affective aversion - Arantxa Vizcaíno-Verdú; Paloma Contreras-Pulido (Cuadernos.info)
Amidst the rise of toxic behavior in online fan communities, this study examines the construction of cross-platform hatedom through social media and the strategies influencers use to navigate hostile digital environments. Using a mixed methods approach, this study analyzes 16,215 comments directed at six influencers using advanced natural language processing techniques and pre-trained AI models. In addition, structured qualitative interviews provided insights into the influencers’ perceptions of their interactions with fans and haters and shed light on their strategies for dealing with hatedom. The results show that hatedoms, characterized by strong affective dislike, vary significantly in their levels of toxicity and emotional polarization on different platforms, including YouTube, X, Facebook, Instagram, TikTok and Twitch. Influencers employ various coping mechanisms, such as ignoring negative interactions, blocking malicious users, and using sarcasm as a defense mechanism. They also emphasize the importance of mental health and often limit their personal engagement to protect their wellbeing. This study highlights the need for a comprehensive, multi-faceted approach to understanding hatedom that combines insights into the polarization of the digital community with the implementation of advanced technological moderation. By prioritizing the mental health and resilience of influencers, it is possible to foster a healthier digital environment amidst the ever-evolving dynamics of fan behavior on social media.